Conrad’s Popular Fictions - Glazzard, Andrew. author. aut Link
VII, 227 p.
Keywords: Detectives, police informers, spies and spymasters, anarchists and terrorists, swindlers: these are the character types explored in Conrad's Popular Fictions. This book shows how Joseph Conrad experimented creatively with genres such as crime and espionage fiction, and sheds new light on the sources and contexts of his work.